The age of maturity - Dale, Richard; Goldberg, Robert (Wonders of the human body, 2002)
Even after we reach maturity, the amazing human body continues to change and adapt. You'll discover how and why in this astonishing look at our senses smell, sight, touch and hearing. See how eyesight works, discover how memory is laid down, watch hair grow and actually see how hearing works including a close up look at the cell that dances when you hear music. Through state of the art imaging techniques, miniscule inside the body cameras, time-lapse photography, computer morphing, digital animation and more the whole family can see, understand and enjoy the science of this astonishing creation, this miraculous machine.. the human body.